Highly Available WebSphere Business Integration Solutions - Redbooks, IBM (I B M, 2004)
Your company has customers on five continents and in every time zone in this on-demand world. Applications throughout the Enterprise run non-stop to support your business. 7x24x365. Or, maybe it is 5x12. If you're going to satisfy your uptime requirement, high availability is an important part of your system design.This IBM Redbooks publication examines valuable design and implementation considerations involved in deploying your highly available WebSphere Business Integration solution, and details the design, implementation, and execution of a sample HA WebSphere Business Integration solution.Please note that the additional material referenced in the text is not available from IBM.